The Meteorological Buoy and Coastal Marine Automated Network for the United States - National Research Council (The National Academies Press, 1998)
Keywords: Earth Sciences

Hydrologic Sciences: Taking Stock and Looking Ahead - National Research Council (The National Academies Press, 1998)
Hydrologic science, an important, interdisciplinary science dealing with the occurrence, distribution, and properties of water on Earth, is key to understanding and resolving many contemporary, large-scale environmental issues. The Water Science and Technology Board used the opportunity of its 1997 Abel Wolman Distinguished Lecture to assess the vitality of the hydrologic sciences by the hydrologic community. The format included focus by lecturer Thomas Dunne on the intellectual vitality of the hydrologic sciences, followed by a symposium featuring several invited papers and discussions. Hydrologic Sciences is a compilation of the Wolman Lecture and the papers, preceded by a summarizing overview. The volume stresses a number of needs for furtherance of hydrologic science, including development of a coherent body of transferable theory and an intellectual center for the science, communication across multiple geo- and environmental science disciplines, appropriate measurements and observations, and provision of central guidance for the field.
Keywords: Earth Sciences

The Atmospheric Sciences: Entering the Twenty-First Century - National Research Council (The National Academies Press, 1998)
Technology has propelled the atmospheric sciences from a fledgling discipline to a global enterprise. Findings in this field shape a broad spectrum of decisions—what to wear outdoors, whether aircraft should fly, how to deal with the issue of climate change, and more. This book presents a comprehensive assessment of the atmospheric sciences and offers a vision for the future and a range of recommendations for federal authorities, the scientific community, and education administrators. How does atmospheric science contribute to national well-being? In the context of this question, the panel identifies imperatives in scientific observation, recommends directions for modeling and forecasting research, and examines management issues, including the growing problem of weather data availability. Five subdisciplines—physics, chemistry, dynamics and weather forecasting, upper atmosphere and near-earth space physics, climate and climate change—and their status as the science enters the twenty-first century are examined in detail, including recommendations for research. This readable book will be of interest to public-sector policy framers and private-sector decisionmakers as well as researchers, educators, and students in the atmospheric sciences.
Keywords: Earth Sciences; Space and Aeronautics

Preventing Reading Difficulties in Young Children - National Research Council (The National Academies Press, 1998)
While most children learn to read fairly well, there remain many young Americans whose futures are imperiled because they do not read well enough to meet the demands of our competitive, technology-driven society. This book explores the problem within the context of social, historical, cultural, and biological factors. Recommendations address the identification of groups of children at risk, effective instruction for the preschool and early grades, effective approaches to dialects and bilingualism, the importance of these findings for the professional development of teachers, and gaps that remain in our understanding of how children learn to read. Implications for parents, teachers, schools, communities, the media, and government at all levels are discussed. The book examines the epidemiology of reading problems and introduces the concepts used by experts in the field. In a clear and readable narrative, word identification, comprehension, and other processes in normal reading development are discussed. Against the background of normal progress, Preventing Reading Difficulties in Young Children examines factors that put children at risk of poor reading. It explores in detail how literacy can be fostered from birth through kindergarten and the primary grades, including evaluation of philosophies, systems, and materials commonly used to teach reading.
Keywords: Education

Cooperating with Nature: Confronting Natural Hazards with Land-Use Planning for Sustainable Communities - Burby, Raymond J. (The National Academies Press, 1998)
This volume focuses on the breakdown in sustainability—the capacity of the planet to provide quality of life now and in the future—that is signaled by disaster. The authors bring to light why land use and sustainability have been ignored in devising public policies to deal with natural hazards. They lay out a vision of sustainability, concrete suggestions for policy reform, and procedures for planning. The book chronicles the long evolution of land-use planning and identifies key components of sustainable planning for hazards. Stressing the importance of balance in land use, the authors offer principles and specific reforms for achieving their visions of sustainability.
Keywords: Explore Science; Earth Sciences; Conflict and Security Issues

Nobel Prize Women in Science: Their Lives, Struggles, and Momentous Discoveries: Second Edition - McGrayne, Sharon Bertsch (The National Academies Press, 1998)
Since 1901 there have been over three hundred recipients of the Nobel Prize in the sciences. Only ten of them—about 3 percent—have been women. Why? In this updated version of Nobel Prize Women in Science, Sharon Bertsch McGrayne explores the reasons for this astonishing disparity by examining the lives and achievements of fifteen women scientists who either won a Nobel Prize or played a crucial role in a Nobel Prize - winning project. The book reveals the relentless discrimination these women faced both as students and as researchers. Their success was due to the fact that they were passionately in love with science. The book begins with Marie Curie, the first woman to win the Nobel Prize in physics. Readers are then introduced to Christiane Nusslein-Volhard, Emmy Noether, Lise Meitner, Barbara McClintock, Chien-Shiung Wu, and Rosalind Franklin. These and other remarkable women portrayed here struggled against gender discrimination, raised families, and became political and religious leaders. They were mountain climbers, musicians, seamstresses, and gourmet cooks. Above all, they were strong, joyful women in love with discovery. Nobel Prize Women in Science is a startling and revealing look into the history of science and the critical and inspiring role that women have played in the drama of scientific progress.
Keywords: Explore Science; Biography and Autobiography

Learning About Assessment, Learning Through Assessment - National Research Council (The National Academies Press, 1998)
The MSEB, with generous support and encouragement from the Carnegie Corporation of New York, seeks to bring discussion of assessment to school-and district-based practitioners through an initiative called Assessment in Practice (AIP). Originally conceived as a series of "next steps" to follow the publication of Measuring Up and For Good Measure, the project, with assistance from an advisory board, developed a publication agenda to provide support to teachers and others directly involved with the teaching and assessment of children in mathematics classrooms at the elementary, middle, and high school levels. In a series of three booklets, AIP presents an exploration of issues in assessment. The first booklet, Learning About Assessment, Learning Through Assessment discusses ways to assist teachers in learning about assessment and how student work can be a rich resource in professional development. The second, Assessment in Support of Instruction, makes a case for aligning assessments with state and district curriculum frameworks and examines ways in which states have shifted their curriculum frameworks and related state assessment programs to reflect the NCTM Standards and other perspectives. The third booklet, Keeping Score, discusses issues to be considered while developing high quality mathematics assessments. This series is specifically designed to be used at the school and school district level by teachers, principals, supervisors, and measurement specialists.
Keywords: Education

Decade-to-Century-Scale Climate Variability and Change: A Science Strategy - National Research Council (The National Academies Press, 1998)
Society today may be more vulnerable to global-scale, long-term, climate change than ever before. Even without any human influence, past records show that climate can be expected to continue to undergo considerable change over decades to centuries. Measures for adaption and mitigation will call for policy decisions based on a sound scientific foundation. Better understanding and prediction of climate variations can be achieved most efficiently through a nationally recognized "dec-cen" science plan. This book articulates the scientific issues that must be addressed to advance us efficiently toward that understanding and outlines the data collection and modeling needed.
Keywords: Environment and Environmental Studies; Earth Sciences

Frontiers of Engineering: Reports on Leading Edge Engineering from the 1997 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1998)
Space may have been called the final frontier, but there are new frontiers to discover every day, and engineers are the ones exploring them. Through groundbreaking research and new technologies, engineers are able to go beyond traditional boundaries to do things that would have been all but impossible just a few years ago. This book, the most recent in a series of publications, describes new and emerging technologies and explains how they were developed and the benefits they will bring. It also offers highlights of the pioneering research and technological work being done by some of the country's emerging leaders in engineering. Topics include biomechanics, sensors and control for manufacturing processes, safety and security issues, decisionmaking tools for design and manufacturing, and intelligent transportation systems.
Keywords: Engineering and Technology

Fostering Research on the Economic and Social Impacts of Information Technology - National Research Council (The National Academies Press, 1998)
The tremendous growth in use of information technology (IT) has led to an increased interest in understanding its social and economic impacts. This book presents examples of crosscutting research that has been conducted to understand the impact of information technology on personal, community, and business activities. It explores ways in which the use of methodology from economics and social sciences contributes to important advances in understanding these impacts. The book discusses significant research issues and concerns and suggests approaches for fostering increased interdisciplinary research on the impacts of information technology and making the results of this research more accessible to the public and policymakers. This volume is expected to influence funding priorities and levels of support for interdisciplinary research of this kind.
Keywords: Computers and Information Technology

People and Pixels: Linking Remote Sensing and Social Science - National Research Council (The National Academies Press, 1998)
Space-based sensors are giving us an ever-closer and more comprehensive look at the earth's surface; they also have the potential to tell us about human activity. This volume examines the possibilities for using remote sensing technology to improve understanding of social processes and human-environment interactions. Examples include deforestation and regrowth in Brazil, population-environment interactions in Thailand, ancient and modern rural development in Guatemala, and urbanization in the United States, as well as early warnings of famine and disease outbreaks. The book also provides information on current sources of remotely sensed data and metadata and discusses what is involved in establishing effective collaborative efforts between scientists working with remote sensing technology and those working on social and environmental issues.
Keywords: Earth Sciences

Paying the Price: The Status and Role of Insurance Against Natural Disasters in the United States - Kunreuther, Howard; Roth, Richard J., Sr. (The National Academies Press, 1998)
This book considers the effectiveness of insurance coverage for low-probability, high-consequence events such as natural disasters—and how insurance programs can successfully be used with other policy tools, such as building codes and standards, to encourage effective loss reduction measures. The authors discuss the reasons for the dramatic increase in insured losses from natural disasters since 1989 and the concern that insurers have about their ability to provide coverage against more such events in the future. It addresses why there has been an increasing demand for hazards insurance, what types of coverage private insurers are willing to offer, and the role of reinsurance and private-/public-sector initiatives at the state and federal levels for providing protection to victims of natural disasters. Detailed case studies of the challenges facing Florida in the wake of Hurricane Andrew in 1992 and California following the Northridge earthquake in 1994 reveal the challenges facing the insurance industry as well as other concerned stakeholders. The National Flood Insurance Program illustrates how a public-/private-sector partnership can mitigate damages and provide financial protection to victims. The book identifies new initiatives for reducing future losses and providing funds for recovery through cooperation by the relevant parties.
Keywords: Explore Science; Earth Sciences; Conflict and Security Issues

Dying to Quit: Why We Smoke and How We Stop - Brigham, Janet (The National Academies Press, 1998)
Historians and scientists a few millennia from now are likely to see tobacco as one of the major bafflements of our time, suggests Janet Brigham. Why do we smoke so much, even when we know that tobacco kills more than a million of us a year? Two decades ago, smoking was on the decline in the United States. Now the decline has flattened, and smoking appears to be increasing, most ominously among young people. Cigar smoking is on the rise. Data from a generation of young smokers indicate that many of them want to quit but have no access to effective treatment. Dying to Quit features the real-life smoking day of a young woman who plans to quit—again. Her comments take readers inside her love/hate relationship with tobacco. In everyday language, the book reveals the complex psychological and scientific issues behind the news headlines about tobacco regulations, lawsuits and settlements, and breaking scientific news. What is addiction? Is there such a thing as an addictive personality? What does nicotine do to the body? How does it affect the brain? Why do people stand in subzero temperatures outside office buildings to smoke cigarettes? What is the impact of carefully crafted advertisements and marketing strategies? Why do people who are depressed tend to smoke more? What is the biology behind these common links? These and many fundamental questions are explored drawing on the latest findings from the world's best addictions laboratories. Want to quit? Brigham takes us shopping in the marketplace of gizmos and gadgets designed to help people stop smoking, from wristwatch-like monitors to the lettuce cigarette. She presents the bad news and the not-so-bad news about smoking cessation, including the truth about withdrawal symptoms and weight gain. And she summarizes authoritative findings and recommendations about what actually works in quitting smoking. By training a behavioral scientist—by gift a writing talent—Brigham helps readers understand what people feel when they use tobacco or when they quit. At a time when tobacco smoke has filled nearly every corner of the earth and public confusion grows amid strident claims and counterclaims in the media, Dying to Quit clears the air with dispassion toward facts and compassion toward smokers. This book invites readers on a fascinating journey through the world of tobacco use and points the way toward help for smokers who want to quit. Janet Brigham, Ph.D., is a research psychologist with SRI International in Menlo Park, California, where she studies tobacco use. A former journalist and editor, she has conducted substance use research at the Johns Hopkins University School of Medicine, the National Institute on Drug Abuse, and the University of Pittsburgh
Keywords: Explore Science; Health and Medicine

Future of the National Weather Service Cooperative Observer Network - National Research Council (The National Academies Press, 1998)
Keywords: Earth Sciences

Developing a Digital National Library for Undergraduate Science, Mathematics, Engineering and Technology Education: Report of a Workshop - National Research Council (The National Academies Press, 1998)
In 1996, the National Science Foundation (NSF) released a report about ways to improve undergraduate science, mathematics, engineering, and technology (SME&T) education. One recommendation called for establishing a digital library, similar to those that are being constructed for many research communities, that would make available electronically a wide variety of materials for improving teaching and learning of SME&T. The NSF asked the National Research Council to examine the feasibility of and issues associated with establishing such a digital national library. In response, an NRC steering committee commissioned a series of papers and convened a workshop to consider these issues. This resulting book delineates the issues that should be considered and provides recommendations to resolve them prior to committing funds.
Keywords: Education; Behavioral and Social Sciences

Ensuring Safe Food: From Production to Consumption - Institute of Medicine (The National Academies Press, 1998)
How safe is our food supply? Each year the media report what appears to be growing concern related to illness caused by the food consumed by Americans. These food borne illnesses are caused by pathogenic microorganisms, pesticide residues, and food additives. Recent actions taken at the federal, state, and local levels in response to the increase in reported incidences of food borne illnesses point to the need to evaluate the food safety system in the United States. This book assesses the effectiveness of the current food safety system and provides recommendations on changes needed to ensure an effective science-based food safety system. Ensuring Safe Food discusses such important issues as: What are the primary hazards associated with the food supply? What gaps exist in the current system for ensuring a safe food supply? What effects do trends in food consumption have on food safety? What is the impact of food preparation and handling practices in the home, in food services, or in production operations on the risk of food borne illnesses? What organizational changes in responsibility or oversight could be made to increase the effectiveness of the food safety system in the United States? Current concerns associated with microbiological, chemical, and physical hazards in the food supply are discussed. The book also considers how changes in technology and food processing might introduce new risks. Recommendations are made on steps for developing a coordinated, unified system for food safety. The book also highlights areas that need additional study. Ensuring Safe Food will be important for policymakers, food trade professionals, food producers, food processors, food researchers, public health professionals, and consumers.
Keywords: Food and Nutrition

Containing the Threat from Illegal Bombings: An Integrated National Strategy for Marking, Tagging, Rendering Inert, and Licensing Explosives and Their Precursors - National Research Council (The National Academies Press, 1998)
In response to the rising concern of the American public over illegal bombings, the Bureau of Alcohol, Tobacco, and Firearms asked the National Research Council to examine possible mechanisms for reducing this threat. The committee examined four approaches to reducing the bombing threat: addition of detection markers to explosives for pre-blast detection, addition of identification taggants to explosives for post-blast identification of bombers, possible means to render common explosive materials inert, and placing controls on explosives and their precursors. The book makes several recommendations to reduce the number of criminal bombings in this country.
Keywords: Conflict and Security Issues

Global Environmental Change: Research Pathways for the Next Decade, Overview - National Research Council (The National Academies Press, 1998)
Keywords: Environment and Environmental Studies

Research Reactor Aluminum Spent Fuel: Treatment Options for Disposal - National Research Council (The National Academies Press, 1998)
The U.S. Department of Energy (DOE) is preparing an environmental impact statement (EIS) for management of aluminum spent fuel from foreign and domestic research reactors, much of which is highly enriched in uranium-235. This EIS will assess the need for additional treatment and storage facilities at the Savannah River Site to accommodate the receipt of this fuel, and it also will assess and select a treatment technology to prepare this fuel for interim storage and eventual shipment to a repository for disposal. This National Research Council book, which was prepared at the request of DOE's Savannah River Office, provides a technical assessment of the technologies, costs, and schedules developed by DOE for eight alternative treatment options and the baseline reprocessing option. It also provides comments on DOE's aluminum spent fuel disposal program, a program that is slated to last for about 40 years and cost in excess of $2 billion.
Keywords: Environment and Environmental Studies

Internet Counts: Measuring the Impacts of the Internet (The National Academies Press, 1998)
Keywords: Computers and Information Technology; Earth Sciences